Performance evaluation of aluminum-in-pot evaporative cooler - Popoola, Olalekan; Issa, Haruna; Ibrahim, Hassan; Omoniyi, Peter; Adegun, Isaac (Revista Brasileira de Engenharia de Biossistemas, 2026)
Cooling applications by refrigeration and air-conditioning require electricity as a source of energy not abundantly available in sub-Saharan African countries. Post-harvest losses of vegetables are caused by poor storage facilities, poor transportation systems, and lack of processing facilities. The current study aimed to evaluate the performance of developed solar-powered Aluminium-in-pot evaporative coolers lined with clay and charcoal blends for the preservation of tomatoes. The evaporative cooler consisted of Aluminium pots inserted into an earthenware mould pot, and the space between the two pots filled with lining media of clay, charcoal, and blends of the two in different ratios. The dry bulb temperature of the ambient air, inner temperatures of the cooling chambers, and relative Humidity were measured using fresh tomatoes as a load for the coolers. The temperature variations of the coolers were recorded for fifteen consecutive days. It was found that the inner temperatures for the five evaporative coolers were significantly different from the dry bulb temperature of the ambient. The temperature of sample E had the lowest temperature range of 19.65 °C to 23.65 °C for the no-load test, 21.15 °C to 25.29 °C for the load–load-test (better boy), and 21.1 to 23.25 °C for the load test (Plum). The daily temperature in the coolers dropped significantly to a range of between 3.4 °C to 10.46 °C with a corresponding daily RH range of 30.93% to 39%. The variations in the efficiency of Sample E were found to be averagely 84% at no load, 72% when loaded with Better Boy and 77% when loaded with Plum tomatoes. The aluminium in pot evaporative cooler could be used for a short-term preservation of tomatoes in remote areas where electricity is not available.